Distribusi lapisan batuan sedimen yang diduga mengandung gas biogenik dengan metode tahanan jenis di Pantai Saronggi, Sumenep, Madura - Lukman Arifin (Geological Agency, 2010)
DOI: 10.17014/ijog.v5i2.97A research on sediments estimated to contain biogenic gas at Saronggi coast Sumenep in Madura, East Java, has been done by using the resistivity method and produced 2-D (two dimensional) cross-sectional along four paths. The results of previous measurements indicate that biogenic gas is present within layers of black shale. It is known that the resistivity values of the black shale bearing biogenic gas is between 0.9-1.3 Ohm m. These resistivity values are used as references to determine the black shale layer bearing gas in four resistivity profiles. The depth of the black shale layers are varies: in profile 1 the depth is between 26.3 and 44.6 m, in profile 2 is between 30 and 45 m, in profile 3 is between 44.6 and 64.8 m, and in profile 4 is between 8,75 and 44,6 m.